Polymorphic Genetic Markers in Patients with Chronic Periodontitis - Sydney Correia Leão; Débora Machado Barreto; Ricardo Vieira da Costa; Rosilene Calazans Soares; Tânia Maria de Andrade Rodrigues (Dentistry, 2016)
Introduction: Chronic periodontitis (CP) is an inflammatory disease caused by the interaction among dental plaque, periodontal tissues, and host immune responses, which causes bone resorption. Interleukin-6 (IL-6) and matrix metalloproteinase-1 (MMP-1) plays an important role in the periodontium destruction. Some authors have studied polymorphisms in these genes but the results were controversial. Objective: The aim of this study was to evaluate the association of polymorphisms in the promoter region of genes IL-6 (-174) and MMP-1 (-1607) with CP in a Northeastern Brazilian population. Methods: A case-control study of 64 cases of CP patients and 25 healthy subjects was performed. Genomic DNA was isolated from buccal mucosa and two single nucleotide polymorphism in IL-6 (-174 G/C) and MMP-1 (-1607 1G/2G) genes were analyzed using polymerase chain reaction followed by restriction fragment length polymorphism analysis (PCR-RFLP). Results: Regarding to results, there were no statistically significant differences between patients with CP and control group, nor to genotypes (p=0.734) nor to alleles (p=0.763), with respect to IL-6 polymorphism. For MMP-1 polymorphism, also we found no statistically significant difference in genotype (p=0.607) and allele (p=0.237) distribution between individuals with CP and the control group. Conclusion: We concluded that the polymorphism of the studied genes were not associated with susceptibility to CP in this Northeastern Brazilian population.